2010
DOI: 10.1073/pnas.1009719107
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differential and functionally active miRNAs in both anaplastic lymphoma kinase (ALK)+and ALKanaplastic large-cell lymphoma

Abstract: Aberrant anaplastic lymphoma kinase (ALK) expression is a defining feature of many human cancers and was identified first in anaplastic large-cell lymphoma (ALCL), an aggressive non-Hodgkin T-cell lymphoma. Since that time, many studies have set out to identify the mechanisms used by aberrant ALK toward tumorigenesis. We have identified a distinct profile of micro-RNAs (miRNAs) that characterize ALCL; furthermore, this profile distinguishes ALK + from ALK − subtypes, and thus points toward potential mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
133
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(145 citation statements)
references
References 41 publications
11
133
1
Order By: Relevance
“…ALK-positive patients were significantly younger than ALK-negative patients, being consistent with the established correlation between ALK expression and young age [7][8][9][10].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…ALK-positive patients were significantly younger than ALK-negative patients, being consistent with the established correlation between ALK expression and young age [7][8][9][10].…”
Section: Discussionsupporting
confidence: 86%
“…Together these findings support the view that primary systemic ALK-positive and ALK-negative ALCL are different disease entities [7][8][9][10].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Importantly, it was also reported that low expression of miR29a, probably achieved through methylation-mediated repression, appeared to play an important regulatory role in MCL-1 overexpression, promoting tumor cell survival by inhibiting apoptosis. Consistently, forced miR29a expression was found to modulate apoptosis through inhibition of MCL-1 expression with concomitant tumor growth reduction in vivo (64).…”
Section: Molecular Pathogenesismentioning
confidence: 50%
“…Fourth, the role of micro-RNAs (miRNAs) has so far been investigated mainly in ALCL. In particular, Merkel et al (64) reported that five members of the miR17-92 cluster were expressed more highly in ALK + ALCL, whereas expression levels of miR155 were more than 10-fold higher in ALK -ALCL. Moreover, miR101 is downregulated in all types of ALCL, a fact of potential therapeutic interest because mTOR is the target of this miRNA.…”
Section: Molecular Pathogenesismentioning
confidence: 99%